1997
DOI: 10.1152/ajpregu.1997.272.1.r16
|View full text |Cite
|
Sign up to set email alerts
|

Lactation alters the effects of conditioned stress on immune function

Abstract: During lactation, endocrine function is altered and stress responses are dampened. Stress effects on immune function are partially determined by endocrine factors; therefore, we assessed whether stress similarly alters immune function during lactation. Sprague-Dawley rats were conditioned by exposure to a tone paired with foot shock (2 sessions, 16 shocks each) prior to breeding or were left undisturbed. Lactating (day 10) (Lac) and nonlactating diestrous virgin controls (C) were killed immediately after reexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 0 publications
4
23
2
Order By: Relevance
“…No differences were found in the magnitude of the CORT response to stress among breeding, nonbreeding, and virgin females. These results contrast with numerous findings in rats, in which lactating dams were shown to have a reduced CORT response to noise, endotoxin, elevated plus maze, and light/dark box tests compared to virgin females (Lightman, 1992; Shanks et al, 1997; Toufexis et al, 1999b; Windle et al, 1997a). Again, our findings might reflect the fact that the breeding females in the present study were concurrently pregnant and lactating, unlike the lactating females used in previous studies of other rodent species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…No differences were found in the magnitude of the CORT response to stress among breeding, nonbreeding, and virgin females. These results contrast with numerous findings in rats, in which lactating dams were shown to have a reduced CORT response to noise, endotoxin, elevated plus maze, and light/dark box tests compared to virgin females (Lightman, 1992; Shanks et al, 1997; Toufexis et al, 1999b; Windle et al, 1997a). Again, our findings might reflect the fact that the breeding females in the present study were concurrently pregnant and lactating, unlike the lactating females used in previous studies of other rodent species.…”
Section: Discussioncontrasting
confidence: 99%
“…Lactational hyporesponsiveness, or blunted responsiveness to stress in lactating females, has been described in a number of mammalian species, including sheep ( Ovis aries ), flying foxes ( Pteropus hypomelanus ), Columbian ground squirrels ( Spermophilus columbianus ), Norway rats ( Rattus norvegicus ), and humans (Deschamps et al, 2003; Hubbs et al, 2000; Lightman, 1992; Reeder et al, 2004; Shanks et al, 1997; Tilbrook et al, 2006; Tu et al, 2005; Windle et al, 1997a). This phenomenon has been characterized most thoroughly in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies by Levine and colleagues showed that responses to footshock and ether stress were reduced in lactating rats (16, 17), and subsequent studies have shown attenuated responses to a wide variety of stresses. These include both psychological stresses—such as noise stress (18), conditioned footshock (19), forced swimming (2022), and restraint (23, 24)—and physical stresses, such as intraperitoneal injection of NaCl (25) or lipopolysaccharide (26), or exposure to ether vapor (23). While this stress hyporesponsiveness is consistent in rodents, the situation is less clear in primates (15).…”
mentioning
confidence: 99%
“…Suppressed responses to stress in pregnancy can be explained by adaptations in both the anterior pituitary and the hypothalamus (Brunton et al, 2005; Russell et al, 2008). Corticotrophs in the pituitary are less sensitive to secretagogs (Shanks et al, 1997; Neumann et al, 1998), and CRH mRNA expression induced by stress is attenuated (Brunton et al, 2005). Moreover, HPA axis responses to immune stress in early mid pregnancy are strong and similar to that in virgins, although activation of hypothalamic vasopressin neurons, rather than CRH neurons, may be more important in the stress response in pregnancy (Ma et al, 2005; Parker et al, 2011).…”
Section: Mechanisms Governing the Hypo-responsiveness To Stress Durinmentioning
confidence: 99%